Control System for Management of Water Supply at a Farm - Doležal, Aleš (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
This paper deals with installing a new system for the supply and management of water on a farm. A PLC from Unitronics company was chosen with the appropriate modules for control and operation. The PLC program has been written in the UniLogic integrated development environment from Unistronics company using ladder language. The new system is controlled and monitored locally by the HMI panel and remotely by the website. The HMI and the website were created in the UniLogic Integrated Development Environment. The thesis also deals with selecting suitable sensors and components for system regulation.
Keywords: PLC, Control system, flowmeter, level sensor